Global Inequalities. - Bradshaw, York W. William (Sociology for a new century., 1996)
This readable, sociologically interpretive book focuses through the lens of stratification and inequality, the authors examine a wide variety of topics - from global economic trends to ethnic conflicts - in four regions: Africa, Asia, Europe, and the Americas. They use academic models and theories to help make sense of current events and help place them in an appropriate context; these are enhanced by the use of lively stories and examples from the press.